The Study of Artemisinin Content in Callus Artemisia annua L. Cultures Elicited with Endophytic Fungi Aspergillus sp. - Farida Yuliani; Widyatmani Sih Dewi; Ahmad Yunus; Usman Siswanto (Universitas Jenderal Soedirman, 2018)
Artemisinin, is a sesquiterpene lactone which is originally extracted from the medicinal plant Artemisia annua L. Artemisinin is a very effective antimalarial agent, however it is produced in very low amounts in plants. Chemical synthesis of artemisinin is complicated and not economically feasible. Researchers often use elicitation methods to increase artemisinin content in a laboratory scale with biotic or abiotic elicitor. This study examined the effect of elicitation using endophytic fungi Aspergillus sp on artemisinin content of callus A. annua cultures. Observations were made on its growth, texture and color, chlorophyll content and dry weight. Fungi were isolated from the stem tissue of A. annua and callus were grown on Murashige and Skoog medium. After 3 weeks of incubation, callus treated with four different elicitors concentration (0, 2, 4, 6 mg/mL). There were significant alterations on callus culture in terms of growth, texture, color and chlorophyll content after elicitation. The results clearly demonstrated that the endophytic fungal elicitor Aspergillus sp could increase artemisinin content but did not affect the callus dry weight of A. annua. The treatment of 4 mg/mL elicitor produced the highest artemisinin content, that increased 7.6 times compared to the control, from 0.0036% to 0.0275%.